Given y = ln((2x+3)/(7x^3 +1)). Find dy/dx

 y = ln(2x+3 / 7x^3 +1)

d/dx(2x+3 / 7x^3 + 1) by quotient rule which is(v.du/dx - u.dv/dx) / v^2  where u=2x+3 and v=7x^3 +1   gives (-27x^3 -63x^2 +2) / (7x^3 +1)^2

so d/dx(ln(2x+3 / 7x^3 +1) = ( (-27x^3 -63x^2 +2) / (7x^3 +1)^2 ) / (2x+3)/(7x^3 +1)

= ((-27x^3 -63x^2 +2) / (7x^3 +1) ) / (2x+3)

= (-27x^3 -63x^2 +2) / (7x^3 +1).(2x+3)

which is the final solution, since it cannot be simplified further.

Answered by Samuel B. Maths tutor

3434 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do you do simple integration?


Integral of 1/(x^3 + 2x^2 -x - 2)


Differentiate f(x)=(x+sin(2x))^4


How do you differentiate simple algebra?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences